Robert of Torigni’s Liber Chronicorum: The Chronography as a textual project in Avranches, Bibliothèque patrimoniale, ms 159 - Gabriele Passabì (Tabularia)
The manuscript Avranches, Bibliothèque patrimoniale, 159 is an extraordinary piece of evidence for the writing of universal chronicles in twelfth century Normandy. It contains the “working-copy” of the chronicle of Robert of Torigni (1106-1186), abbot of Mont Saint-Michel, an update and continuation of the universal chronicle of Sigibert of Gembloux (1030-1112). The purpose of this paper is to elucidate the visual and textual features that make Avranches 159 Robert of Torigni’s Liber Chronicorum. With his chronography, Robert of Torigni aimed to join the authoritative Eusebius-Jeromian tradition of chronicle-writing. Whilst maintaining the visual unity of the manuscript, Robert altered its chronographic structure to include the Anglo-Saxon and the Anglo-Norman past as the realization of the divine plan. As contextualized in the visual totality of Avranches 159, Robert of Torigni’s chronography appears as a sophisticated textual project that aimed to integrate Henry II’s dynastic past into universal history to enhance the legitimacy of the English king.